Effect of sodium-glucose Co-transporter 2 inhibitors on coronary microcirculation - Chen, Shaoxin; Ou, Weiqian; Gan, Shuguang; Chen, Lixian; Liu, Baohua; Zhang, Zhenhong (Frontiers in Pharmacology, 2025)
Coronary microvascular disease (CMVD) has emerged as a new target for the occurrence and development of heart failure treatment. Various indicators such as Index of Microvascular Resistance, Coronary Flow Reserve, Microvascular Resistance Reserve, Hyperemic Microvascular Resistance and Coronary Flow Velocity Reserve can be used to assess CMVD. Coronary microcirculation dysfunction is one of the important pathogenic mechanisms of heart failure. Sodium-Glucose Co-Transporter 2 (SGLT2) Inhibitors have been widely used in the treatment of various types of heart failure, but their specific pharmacological mechanisms are not yet fully understood. Studies have shown that SGLT2 inhibitors may be involved in the pathophysiology of CMVD by regulating cellular pathophysiological processes such as oxidative stress, mitochondrial function, energy metabolism, vascular genesis, and signalling pathways. Therefore, coronary microvascular dysfunction may be one of the treatment targets of using SGLT2 inhibitors in heart failure. Several animal experiments have found that SGLT2 inhibitors can improve microcirculatory dysfunction. However, the results of several clinical trials on the effects of SGLT2 inhibitors on coronary microcirculation have been different. Therefore, it is still lack of conclusive evidence on the effects of SGLT2 inhibitors on microcirculatory dysfunction. This review aims to summarize the completed and ongoing experiments regarding the effects of SGLT2 inhibitors on coronary microcirculation, in order to better elucidate the impact of SGLT2 inhibitors on microcirculation. It seeks to provide valuable information for the pharmacological mechanisms of SGLT2 inhibitors, the study of diseases related to coronary microcirculation disorders, and the treatment of heart failure.